Preventable trauma death rate in Daegu, South Korea - Sungbae Moon; Suk Hee Lee; Hyun Wook Ryoo; Jong Kun Kim; Jae Yun Ahn; Sung Jin Kim; Jae Cheon Jeon; Kyung Woo Lee; Ae Jin Sung; Yun Jeong Kim; Dae Ro Lee; Byung Soo Do; et al. (Clinical and Experimental Emergency Medicine, 2015)
Objective This study investigated the preventable death rate in Daegu, South Korea, and assessed affecting factors and preventable factors in order to improve the treatment of regional trauma patients. Methods All traumatic deaths between January 2012 and December 2012 in 5 hospitals in Daegu were analyzed by panel review, which were classified into preventable and non-preventable deaths. We determined the factors affecting trauma deaths and the preventable factors during trauma care. Results There were overall 358 traumatic deaths during the study period. Two hundred thirty four patients were selected for the final analysis after excluding cases of death on arrival, delayed death, and unknown causes. The number of preventable death was 59 (25.2%), which was significantly associated with mode of arrival, presence of head injury, date, and time of injury. A multivariate analysis revealed that preventable death was more likely when patients were secondly transferred from another hospital, visited hospital during non-office hour, and did not have head injuries. The panel discovered 145 preventable factors, which showed that majority of factors occurred in emergency departments (49.0%), and were related with system process (76.6%). Conclusion The preventable trauma death rate in Daegu was high, and mostly process-related.